Desorption isotherms of sweetened maturing coconut meat at different temperatures - Diamante, Lemuel M. (Annals of Tropical Research, 2001)
The main objective of the study was to obtain the desorption isotherms of sweetened maturing coconut meat at different temperatures (50, 60 and 70°C). A static gravimetric technique was used for the desorption isotherm determination of the material using a standard procedure. Results revealed that the desorption isotherms of sweetened maturing coconut meat were of type III according to the BET classification, The increase in the amount of sorbed water at a given water activity with the decrease in temperature is consistent with the theory of physical adsorption. A modified Caurie equation can describe the effect of temperature. on the desorption isotherms of sweetened maturing coconut.. Using this equation for analysis, the results suggest that when drying of sweetened maturing coconut meat is done at higher temperatures (above 70°C) the equilibrium moisture content (EMC) of the sample is not greatly affected and attains a value of less than 1% dry basis. However, when drying is done at lower temperatures (below 60°C), the relative humidity of the drying air is higher and giving higher EMC of the sample. The net heat of desorption for sweetened maturing coconut meat increases as the moisture content decreases which is expected for most food products. The relationship between the net heat of desorption and moisture content of the product can be expressed by an exponential equation. Using this equation for analysis, the results showed that as the final moisture content of the product decreases the energy requirement increases.